Multimodal literacy in digital game-based learning among secondary school students in China - Shen, Yanan (2024)
In the digital world with a ubiquitous multimodal media-saturated environment, multimodal literacy has been an integral part of school literacy education. Multimodal literacy expands literacy from basic language skills to multiple abilities of critical consuming and creative producing multimodal texts for communication. Digital games, a prevalent type of digital media practice in the youth’s lives, can ideally facilitate students’ multimodal literacy learning and connect school education with students’ lifeworld. However, in China, especially in less-developed regions, multimodal literacy is marginalised in classrooms. Similarly, digital games are undervalued or even distrusted despite their ongoing popularity, leaving their pedagogical potential underutilised. Hence, this study aims to explore how Chinese secondary students develop multimodal literacy in digital game-based learning (DGBL) in an underdeveloped context, focusing on students’ multimodal literacy development as critical consumers in game analysis and as creative producers in game paratext design, and challenges in their learning process. To achieve the research objectives, this research employed the qualitative case study approach for a comprehensive and in-depth understanding of students’ multimodal literacy within a specific social context. The main component is a 16-session digital game-based multimodal literacy program launched in a suburban school in northern China as a supplement for Chinese language classes. A total of 16 students from eighth grade participated in this program, engaging in collaborative digital gameplay and analysis followed by game video design, with the researcher’s systematic guidance and two teachers’ assistance. Multiple data-collection methods were applied, encompassing participant observation, interviews, field notes, and the studentauthored electronic portfolios and game videos. The data went through multimodal discourse analysis and thematic analysis, yielding extensive research findings. The findings reveal students’ multimodal literacy development from causal players to critical consumers, demonstrating enhanced knowledge and ability to analyse multimodal game texts and gaming experience across representation, engagement, and organisation dimensions. Besides, they developed multimodal literacy to innovatively apply multiple semiotic modes and digital tools to design game paratexts as creative producers, expressing original ideas from representational, interpersonal, and compositional perspectives. The researcher’s guidance played a crucial role throughout their learning process. Moreover, four main challenges include processing complex multimodal information in multi-tasking, the lack of relevant knowledge and skills, challenging teamwork, and external constraints at school.In conclusion, this study contributes empirical evidence to substantiate that DGBL offers fertile ground and abundant learning resources for secondary students’ critical and creative engagement in multimodal literacy practice, thus strengthening their multimodal literacy. Meanwhile, instructors’ systematic interventions are crucial in incorporating DGBL in literacy classrooms to transform these possibilities into reality and address variations among students’ multimodal literacy levels. Admittedly, incorporating digital games to promote multimodal literacy education is challenging in less-developed regions in China with the entrenched exam-oriented education system and limited educational resources. Consequently, joint efforts from diverse stakeholders are necessary to provide students with equitable access to digital technologies and additional training for effective utilisation, thus preparing them for active participation in the future.